The The effect Of Slow Exercises On Learning And retaining Artistic Performance In Walking. - Hussein, Monther (Journal of Physical Education, 2010)
The problem of the research lies in the lack of teaching model the suits athletes of the ages (10 – 12) years as well as the lack of teaching walking sport in athletics in all training centers. The aim of the research is to identify the effect of slow exercises on learning the artistic performance of walking for young athletes. In addition to that it aimed at identifying retention of this artistic performance of walking in young athletes. The researcher hypothesized statistical differences in pre and posttests in favor of the experimental group in learning the artistic performance of walking. There are also statistical differences in the posttests and retention of the experimental group. The subjects were (10) track and field athletes of the ages 10 – 12 years old. The experiment lasted from 23/9/2008 till 16/11/2008 in the training centers in Al Seder city, the track of the college of physical education, and Al Shaab stadium. Two pilot studies were conducted and they were followed by applying the experimental training program. The training program lasted for 6 weeks with 3 training sessions per week. The program included 4 exercises with four repetitions for each exercises. The training session lasted for 45 minutes. Many tests were used like 50m walking for measuring the accuracy of walking as well as retention test for measuring forgetting performance. He also used proper statistical methods to treat the results like standard deviation, mean, t tests and retention. The researcher concluded statistical differences between pre and posttests in favor of the experimental group and in all variables of artistic performance. There are also statistical differences in the posttests in favor of the posttests and retention for the experimental group. There are also positive effects on retaining the artistic performance. Finally the researcher recommended using slow exercises as a base for teaching artistic performance in walking in all training centers for athletics and for the ages 10 – 12 years old. In addition to that he recommended making similar studies about slow exercises and performance retention on older subjects in training centers